2008
DOI: 10.1088/0022-3727/41/10/102008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of microwave heating on phase transformations in nanostructured alumina

Abstract: Microwave influence on phase transformations in nanostructured alumina has been investigated in a comparative study. It has been found that microwave heating results in a lower phase transformation temperature, not affecting other features of the phase transformation process such as grain size and the effect of dopant addition. For the first time, the dependence of the effect on microwave intensity has been characterized quantitatively. Unexpectedly, this dependence turns out to be non-monotonic, and the phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…It was shown in [1,2,[8][9][10][11][12] that changes in semiconductor defect subsystem under action of microwave radiation may be of thermal as well as nonthermal character. The thermal mechanisms of action of microwave radiation may be classified into three groups for convenience [8,9].…”
Section: Resultsmentioning
confidence: 99%
“…It was shown in [1,2,[8][9][10][11][12] that changes in semiconductor defect subsystem under action of microwave radiation may be of thermal as well as nonthermal character. The thermal mechanisms of action of microwave radiation may be classified into three groups for convenience [8,9].…”
Section: Resultsmentioning
confidence: 99%
“…Few research works have been reported in the literature about the effect of microwaves on the g to a phase transformation in transition alumina powders [17,38]. Noteworthy is the study conducted by Rybakov et al [16] that also showed a decrease of the temperature of phase transformation. Two assumptions were proposed by Rybakov et al to explain this effect.…”
Section: Discussionmentioning
confidence: 99%
“…Possible benefit of microwaves has been investigated by a few authors. Rybakov et al [16] observed an 80 C decrease of the temperature of phase transformation under microwaves and they found that the extent of phase transformation depends on the microwave intensity. On the contrary, Freim et al [17] obtained neither an effect of microwaves on the g to a phase transformation nor a smaller grain size after similar densification in comparison with conventional sintering.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of the microwave field intensity on the phase transformations [9] and the evolution of porous structure [10] in nanopowder alumina compacts was examined jointly with the Bayreuth University (Germany). The samples were made of nanosized alumina powder produced by an electric explosion of conductors [11] at the Institute of Electrophysics, Ural Division, Russian Academy of Sciences (Ekaterinburg).…”
Section: Thermally Balanced Microwave Heating With Power Variationmentioning
confidence: 99%
“…Therefore, the dependence of phase transformations on the microwave field intensity is nonmonotonic: the maximum effect is observed at moderate field intensity. The nonmonotonic dependence may be due to at least two mechanisms of the nonthermal effect of the microwave field on the nucleation and growth of a new phase, which act in different directions at different microwave powers [9].…”
Section: Thermally Balanced Microwave Heating With Power Variationmentioning
confidence: 99%